2018
DOI: 10.25135/rnp.66.18.02.221
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Insect Repellent Activity of Cyclocolorenone Obtained from the Red Alga Laurencia intricata

Abstract: Three known secondary metabolites were isolated from the organic extract of Laurencia intricata. Their structures were identified by NMR and MS experiments and comparison with the literature data. An aromadendrane sesquiterpene, (+)-cyclocolorenone showed strong repellent activity against the maize weevil Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) adults. It had the same activity as natural insecticides, pyrethrins, with a ED50 value of 2.0 g/cm 2 . This is the first report of insect repellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…Laurinterol is a cyclolaurane-type halogenated sesquiterpene, which is the main secondary metabolite in the acetic acid-ethyl ester extract of the red algae, Laurencia nidifica [112] . Ishii et al [113] for the first time reported its repelling activity on Sitophilus zeamais, insecticidal activity on Reticulitermes speratus, acetylcholinesterase inhibitory activity and toxicity to Artemia salina. The findings suggest that L. nidifica may be a good source of bioactive natural products with insecticidal activity.…”
Section: Terpenoidsmentioning
confidence: 99%
“…Laurinterol is a cyclolaurane-type halogenated sesquiterpene, which is the main secondary metabolite in the acetic acid-ethyl ester extract of the red algae, Laurencia nidifica [112] . Ishii et al [113] for the first time reported its repelling activity on Sitophilus zeamais, insecticidal activity on Reticulitermes speratus, acetylcholinesterase inhibitory activity and toxicity to Artemia salina. The findings suggest that L. nidifica may be a good source of bioactive natural products with insecticidal activity.…”
Section: Terpenoidsmentioning
confidence: 99%
“…Laurinterol was previously isolated from Laurencia nidi ca and its insecticidal activity on termite Reticulitermes speratus was evaluated (LD 50 = 2.20 µg/insect) (Ishii et al 2017).…”
Section: Identi Cation Of Activementioning
confidence: 99%
“…[1] The red algal genus Laurencia is known for its richness in halogenated secondary metabolites, which are structurally unique and have various biological activities, such as antifouling, anti-insect, and antibacterial activities. [2][3][4][5][6] This genus is primarily distributed in tropical, subtropical, and temperate waters near the low-tide line and deep sea, with approximately 140 species worldwide and 24 species in Japan. [7] Among the terpenoids isolated and identified from this genus, diterpenoids are abundant and exhibit diverse structures, with the majority containing halogens, particularly bromine and chlorine.…”
Section: Introductionmentioning
confidence: 99%
“…Marine red algae produce specific chemical components that protect them against feeding behavior from predators and bacterial infection to survive in complex marine ecosystems, creating halogenated secondary metabolites with unique biological properties and agricultural value [1] . The red algal genus Laurencia is known for its richness in halogenated secondary metabolites, which are structurally unique and have various biological activities, such as antifouling, anti‐insect, and antibacterial activities [2–6] . This genus is primarily distributed in tropical, subtropical, and temperate waters near the low‐tide line and deep sea, with approximately 140 species worldwide and 24 species in Japan [7] .…”
Section: Introductionmentioning
confidence: 99%